Proteinska lepila na osnovi soje, krvi in kazeina nekoč in danes - Vnučec, Doroteja (Acta silvae et ligni, 2017)
This paper reviews the development of protein adhesives, specifically soy, blood, and casein adhesives. It addresses the formulations and bonding technologies of these protein adhesives from 1930 to 1960, and current commercial formulations. Between the 1930s and 1960s the consumption and technological refinements of protein adhesives were at their peak. Addressing current formulations and bonding technologies, the emphasis is on the soy adhesives, since they are used in industry of decorative plywood, particleboard, fibreboard, and engineered wood flooring. Today, casein is used only in adhesives for fire-resistant wood doors, while animal blood is no longer utilised in adhesives. Although the formulations from 1930 to 1960 do not meet current standards and are no longer used today, all described technologies are still usable and may be reintroduced if the world's crude oil resources are dried up.
Keywords: protein adhesives; proteinska lepila; les; wood; soja; soy; blood; kri; kazein; casein; formulacije; formulations; bonding technology; tehnologija lepljenja